THE AGING SEMANTIC DIFFERENTIAL PREDICTS CONTACT WITH OLDER ADULTS AND KNOWLEDGE OF AGING. (11th November 2018) - Intrieri, R
Abstract: Previous studies have demonstrated a significant relationship between attitudes toward aging and knowledge of aging and contact with older adults. However, most of these studies are limited by their experimental design. Previous studies examined how attitudes may influence knowledge and contact with older adults without considering verbal ability as a potential covariate. Vocabulary is generally thought to be the best single indicator of intelligence and is included in most assessments of intellectual functioning. The current study assesses the relationships between the four factors of Aging Semantic Differential (ASD; Instrumentality, Autonomy, Acceptability, and Integrity) and knowledge of aging and frequency of contact with older adults while using biological sex, age, and verbal ability as a covariates. The convenience sample consisted of 471 undergraduate students, with a mean age of 19.68 (SD= 2.278). Two hierarchical regression models were used to examine how well the ASD predicted knowledge of aging and self-reported contact with older adults while controlling for verbal ability. A hierarchical regression model using knowledge of aging as the dependent variable was statistically significant F(5, 465)= 10.386, p<0.0001, R2=.10 with Verbal Ability β= 0.219, p<0.0001 and ASD-Integrity β=0.219, p<0.0001as significant predictors. Regression model two used contact with older adults as the dependent variable was statistically significant F(6, 462)=12.523, p=.023, R2=.031. Significant effects were only observed for ASD-Instrumental, Acceptance, and Integrity (β=-0.115, p=0.041 Acceptance β= -0.155, p=0.019; Integrity β= 0.160, p=0.022, respectively). This study provides evidence that verbal ability influences knowledge of aging but does not predict contact with older adults.